The art of caring: health, spirituality and education - Santana Santos, Franklin; Incontri, Dora (O Mundo da Saúde, 2010)
Caring is one of the bases of Mother Nature. Most species of our planet, be they vegetal or animal, has in some degree developed the apparently innate characteristic of caring, which seems to be linked to the very maintenance and sustaining of life. While in vegetables the ability of caring is linked to self-care, in the sense of preserving life, it is developed and improved and reaches its apex in the human species. When observing the process of development and evolution of life, we see that the ability of caring achieved an apparent competitive advantage in the evolution process. It seems it made such a symbiosis with Life itself that it penetrated its very essence. Thus, now Life and Caring are so intertwined that became synonymous in the evolutionary process. Caring seems therefore to be a refinement and one of the purposes of life, but could only be understood in this sense if we consider it from a perspective of transcendence or a design of its Creator.